Child 44 - Smith, Tom Rob. (New York : Grand Central Pub, 2011)
Stalin's Soviet Union is an official paradise, where citizens live free from crime and fear only one thing: the all-powerful state. Defending this system is idealistic security officer Leo Demidov, a war hero who believes in the iron fist of the law. But when a murderer starts to kill at will and Leo dares to investigate, the State's obedient servant finds himself demoted and exiled. Now, with only his wife at his side, Leo must fight to uncover shocking truths about a killer-and a country where "crime" doesn't exist.
Includes bibliographical references.
Includes "Reading Group Guide" (p. [441]-444); c2012.
Includes an excerpt from Agent 6 (p. [446]-468); c2012.
Keywords: Secret service -- Soviet Union -- Fiction; Soviet Union -- History -- 1925-1953 -- Fiction; Secret service; Soviet Union; 1925 - 1953; Fiction; History; Suspense fiction